Crosstalk between endophytes and a plant host within information-processing networks - Kozyrovska, N.O. (Вiopolymers and Cell, 2013)
Plants are heavily populated by pro- and eukaryotic microorganisms and represent therefore the tremendous complexity as a biological system. This system exists as an information-processing entity with rather complex processes of communication, occurring throughout the individual plant. The plant cellular information-processing network constitutes the foundation for processes like growth, defense, and adaptation to the environment. Up to date, the molecular mechanisms, underlying perception, transfer, analysis, and storage of the endogenous and environmental information within the plant, remain to be fully understood. The associated microorganisms and their investment in the information conditioning are often ignored. Endophytes as plant partners are indispensable integrative part of the plant system. Diverse endophytic microorganisms comprise «normal» microbiota that plays a role in plant immunity and helps the plant system to survive in the environment (providing assistance in defense, nutrition, detoxification etc.). The role of endophytic microbiota in the processing of information may be presumed, taking into account a plant-microbial co-evolution and empirical data. Since the literature are beginning to emerge on this topic, in this article, I review key works in the field of plant-endophytes interactions in the context of information processing and represent the opinion on their putative role in plant information web under defense and the adaptation to changed conditions. Рослини густо населені про- та евкаріотними мікроорганізмами і, отже, являють собою біологічну систему надзвичайної складності. Ця система з доволі непростими процесами комунікації, що відбуваються вздовж усієї рослини, існує для обробки інформації. Мережева обробка інформації у рослин є основою для таких процесів, як ріст, захист і пристосування до навколишнього середовища. Молекулярні механізми, що лежать в основі сприйняття, передачі, аналізу та зберігання ендогенної і зовнішньої інформації всередині рослини, ще належить повністю з’ясувати. Асоційовані з рослиною мікроорганізми та їхній внесок в обробку інформації дослідники часто ігнорують. Ендофіти як партнери рослини є необхідною інтегративною частиною її системи. Різноманітні ендофітні мікроорганізми являють собою «нормальну» мікрофлору, яка відіграє важливу роль в імунітеті рослин і допомагає їм вижити у навколишньому середовищі (захист, живлення, детоксикація тощо). Певну роль ендофітної мікробіоти в обробці інформації можна припустити, беручи до уваги ко-еволюцію рослинно-мікробних систем та емпіричні дані. Оскільки в літературі починають з’являтися публікації на цю тему, в представленому огляді розглянуто ключові роботи в галузі взаємодії рослин з ендофітами у контексті обробки інформації і висловлено думку стосовно їхньої прогнозованої ролі в інформаційній мережі рослин за умов захисту та пристосування останніх до змінених умов та налаштування відповідної поведінки рослини. Растения густо населены про- и эукариотическими микроорганизмами и, таким образом, представляют собой биологическую систему чрезвычайной сложности. Эта система с довольно непростыми процессами коммуникации, проходящими в растении, существует для обработки информации. Сетевая обработка информации у растений служит основой для таких процессов, как рост, защита и приспособление к окружающей среде. Молекулярные механизмы, лежащие в основе восприятия, передачи, анализа и сохранения эндогенной и внешней информации внутри растения, еще предстоит выяснить. Ассоциированные с растением микроорганизмы и их вклад в обработку информации исследователи часто игнорируют. Эндофиты как партнеры растений являются необходимой интегративной частью ее системы. Разнообразные эндофитные микроорганизмы – это «нормальная» микрофлора, выполняющая важную роль в иммунитете растений и помогающая им выжить в окружающей среде (защита, питание, детоксикация и др.). Определенную роль эндофитной микробиоты в обработке информацмм можно предположить, приняв во внимание ко-эволюцию растительно-микробных систем, а также эмпирические данные. Поскольку в литературе начинают появляться публикации на эту тему, в представленном обзоре рассмотрены ключевые работы в области взаимодействия растений с эндофитами в контексте обработки информации и изложено мнение об их прогнозируемой роли в информационной сети растений в условиях защиты и проспособления последних к измененным условиям и настройке соответствующего поведения растения.